Eating skills in children with autism via video modeling: an evaluation of face and content validation - Ismail, Nurul Khairani; Hosshan, Hasrul; Abd Aziz, Nurbieta; Masnan, Abdul Halim; Che Rozubi, Norsayyidatina; Md Zalli, Mohd Muslim (International Journal of Public Health Science (IJPHS), 2024)
Children with autism spectrum disorder (ASD) may have their eating habits impacted by their traits, such as difficulty remaining seated at the table and exhibiting behaviors during mealtime. This often worries parents and causes stress and anxiety. Given video modeling's potential in helping children with ASD, experts should evaluate its effectiveness for teaching eating skills due to limited research in this area. Thus, the study aim to evaluate the validity of the developed videos of eating skills for children with ASD. For face validity, a focus group discussion was held to obtain experts' feedback on the eating skills video and was transcribed verbatim. Otherwise for content validity, the experts received content validity assessment forms and guidelines via email and the results was analysed using Microsoft excell. Face validity revealed four themes: suitability of videos, video quality and clarity, video instructions suitability, task analysis arrangement, and "other" recommendations. On the other hand, Video 1 and Video 2 scored 0.93 for relevance, clarity, simplicity, and ambiguity for the S-CVI/Ave (scale-level content validity index based on the average method) which was considered acceptable. Video 3 received a satisfactory S-CVI/Ave score of 0.93 for relevance, simplicity, and ambiguity, but its clarity score at 0.91, and still within an acceptable range, though not particularly high. As a conclusion, all task analyses for the videos met the requirement to be considered acceptable. Addressing the suggestions for improvement can increase the video's efficacy in teaching eating skills and relieving parents' concerns.